2008
DOI: 10.1097/aog.0b013e3181626d1b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral and Transdermal Hormonal Contraception on Vascular Risk Markers

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 21 publications
2
38
2
4
Order By: Relevance
“…There are published data regarding the use of COCs and their impact on vWF level that confirm our finding. 25,37 The FVII activity levels were higher among both CHC user groups, as compared to the control group. The CVC users in our study had a lower level of FVII than the COC users (though not statistically significantly lower).…”
Section: Discussionmentioning
confidence: 95%
“…There are published data regarding the use of COCs and their impact on vWF level that confirm our finding. 25,37 The FVII activity levels were higher among both CHC user groups, as compared to the control group. The CVC users in our study had a lower level of FVII than the COC users (though not statistically significantly lower).…”
Section: Discussionmentioning
confidence: 95%
“…The dosing and formulation of the patch medication is also important, as recently demonstrated for a contraceptive patch. 10 At this time, surrogate end point data, when taken together with the observational data available, is not sufficient to support safety from the venous thrombosis perspective. A large clinical trial or further observational studies supporting this hypothesis are needed.…”
Section: See Accompanying Article On Page 340mentioning
confidence: 99%
“…However, in a recent randomized, investigator-blinded, crossover clinical trial of 24 women 18 to 35 years of age, transdermal and oral contraceptives had similar statistically significant adverse effects on vascular risk markers. 709 Recent assessment of the etonogestrel-releasing implant suggested that these implants did not induce a prothrombotic state during the first 6 months of use. 710 Confounding factors such as vascular health, timing of medication administration, route of delivery, smoking, diabetes mellitus, insulin resistance, obesity, and genetically increased risk for thromboembolism affect the risk of thrombosis in individual patients.…”
Section: Oral Contraceptivesmentioning
confidence: 99%